Is Inflation Target Announced by Bank Indonesia the Most Accurate Inflation Forecast? - Rachman, Faisal (Economics and Finance in Indonesia, 2016)
This article investigates whether following Bank Indonesia's explicit inflation targets (forward-looking) is a more accurate method of predicting inflation rate in Indonesia than forecast methods utilizing past information of macroeconomic data (backward-looking). The analysis is conducted by performing naive, univariate, and multivariate time-series models with an out-of-sample forecast evaluation period of January 201-December 2016. It is found that the backward-looking approach outperforms the forward-looking approach at all forecast horizons, indicating that Bank Indonesia still does not succeed to anchor inflation expectation towards the desired level.